Female genital mutilation: Overview and dermatologic relevanceCapsule Summary - Ilhan Esse, BA; Colin M. Kincaid, BS; Carrie Ann Terrell, MD; Natasha A. Mesinkovska, MD, PhD (Elsevier, 2024)
Female genital mutilation (FGM) is a common cultural practice, which involves the partial or complete removal of the external female genitalia. With increasing immigration from regions where the practice is endemic, there has been a growing prevalence of FGM in the United States and other developed nations. However, most medical professionals lack the baseline knowledge regarding FGM and its associated health complications. Given this increasing trend, dermatologists should anticipate an increasing number of patients with a history of FGM in their practice. While some of the obstetric, gynecologic, and psychologic consequences of FGM have been well-reported, the dermatologic findings are less characterized. Thus, this review article aims to provide dermatologists with a fundamental understanding of the prevalence, cultural significance, and health implications of FGM with a focus on the associated dermatological findings and provides recommendations on how dermatologists can address this sensitive matter.